Epibrassinolide-induced apoptosis regardless of p53 expression via activating polyamine catabolic machinery, a common target for androgen sensitive and insensitive prostate cancer cells - Çoker Gürkan, Ajda; Palavan Unsal, Narçin; ARISAN, ELİF DAMLA; YERLİKAYA, PINAR OBAKAN (Wiley-Blackwell, 111 River St, Hoboken 07030-5774, Nj Usa, 2014)
BACKGROUNDEpibrassinolide (EBR), is a member of the brassinosteroids (BR), has been shown as an apoptotic inducer in different cancer cell lines. We previously showed that EBR induced apoptosis by activating polyamine catabolic pathway, which lead to the accumulation of cytotoxic compounds such as hydrogen peroxide and aldehydes in LNCaP and DU 145 prostate cancer cells. However, we found that LNCaP prostate cancer cells expressing functional androgen receptor (AR) was found more sensitive to EBR than those with non-functional AR (DU 145 cells). RESULTSTo better understand the apoptotic effect of EBR, we aimed to investigate the cellular responses in p53 null, PC3 prostate cancer cells. We showed that EBR induced mitochondria-mediated and caspase-dependent apoptosis in wt and p53 stable transfected PC3 cells, which suggesting that EBR-induced apoptosis regardless of p53 expression. In addition, inhibition of p53 by pifithrin- orthe activation of Mdm2 by Nutlin-3 co-treatment did not alter EBR induced PARP cleavage. Furthermore, EBR treatment was also induced apoptosis in both LNCaP(wt p53) and DU 145 (mt p53)cells, respectively. These all findings verified that EBR-induced apoptosis regardless of p53 expression. The PA catabolic pathway was also altered in PC3 cells causing the generation of reactive oxygen species (ROS) and intracellular PA pool decrease. However, the silencing of spermidine-spermineacetyltransferase (SSAT), a key enzyme at polyamine catabolic machinery prevented the EBR-induced apoptosis. CONCLUSIONSTherefore, we concluded that EBR-induced apoptosis was mainly related with PA catabolic pathway and independent from p53 expression. Prostate 74: 1622-1633, 2014. (c) 2014 Wiley Periodicals, Inc.
Keywords: epibrassinolide; apoptosis; polyamines; prostate cancer; Spermine Oxidation-Products; Bax